Cybercrime, cyberterrorism, and cyberwarfare : critical issues in data protection for health services information systems - Ramsaroop, Peter...[et al] (PAHO WashingtonUS, 2003)
Addresses the need to increase awareness of critical issues in data protection for Health Services Infornation Systems related to cyber security requirements and concerns.